Ren (仁 ), the benevolent thought of traditional Chinese medicine - Anwen Zheng (Wolters Kluwer Health/LWW, 2019)
This article offers a brief introduction to the evolution of Ren(仁), which is not only the core of Confucian ethics but also the top moral principle observed by traditional Chinese medicine doctors, holding that feasible solutions to cultural conflicts could be worked out under the guidance of Ren.